A Fast, Low‐Temperature Synthesis Method for Hexagonal YMnO3: Kinetics, Purity, Size and Shape as Studied by In Situ X‐ray Diffraction. Issue 42 (12th May 2020) - Marshall, Kenneth P.; Blichfeld, Anders B.; Skjærvø, Susanne L.; Grendal, Ola G.; van Beek, Wouter; Selbach, Sverre M.; Grande, Tor; Einarsrud, Mari‐Ann
Abstract: The reaction mechanisms, phase development and kinetics of the hydrothermal synthesis of hexagonal‐YMnO3 from Y2 O3 and Mn2 O3 using in situ X‐ray diffraction are reported under different reaction conditions with temperatures ranging from 300 to 350 °C, and using 1, 5 and 10 m KOH, and 5 m NaOH mineraliser. Reactions initiated with Y2 O3 hydrating to Y(OH)3, which then dehydrated to YO(OH). Higher temperatures and KOH concentrations led to faster, more complete dehydrations. However, 1 m KOH led to YO(OH) forming concurrently with Y(OH)3 before Y(OH)3 fully dehydrated but yielded a very low phase purity of hexagonal‐YMnO3 . Using NaOH mineraliser, no YO(OH) was observed. Dehydration also initiated at a higher temperature in the absence of Mn2 O3 . The evolution of Rietveld refined scale factors was used to determine kinetic information and approximate activation energies for the reaction. The described hydrothermal synthesis offers a fast, low‐temperature method for producing anisometric h‐YMnO3 particles. Abstract : Phase development : The hydrothermal synthesis of hexagonal YMnO3 from Y2 O3 and Mn2 O3 was investigated by in situ X‐ray diffraction. Using this technique, information on mechanism, kinetics and thermodynamics of the reaction has been extracted, as well as the impact that mineraliser type and concentration, and temperature have on these properties.